Beyond the Islamicate Chancery: Archives, Paperwork, and Textual Encounters across Eurasia, a Preface. Issue 3 (December 2020) - Sartori, Paolo
Abstract: This thematic issue of Itinerario brings together a selection of papers presented at the international conference Beyond the Islamicate Chancery: Archives, Paperwork, and Textual Encounters across Eurasia, which was held at the Austrian Academy of Sciences in Vienna in early October 2018. The conference was the third instalment in a series of collaborations between the Institute of Iranian Studies at the Austrian Academy of Sciences and the University of Pittsburgh examining Islamicate cultures of documentation from different angles. Surviving precolonial and colonial chancery archives across Eurasia provide an unparalleled glimpse into the inner workings of connectivity across writing cultures and, especially, documentary practices. This particular meeting has attempted to situate what has traditionally been a highly technical discipline in a broader historical dialogue on the relationship between state power, the archive, and cultural encounters.